Influence of electroblasting breaker parameters on electric spark discharge characteristics in a circuit with an inductive-capacitive energy store - Dubovenko, K. V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2012)
Influence of electroblasting breaker parameters (switch inductance, foil length and width) on electric spark discharge characteristics in a circuit with an inductive-capacitive energy store and plasma load is studied by means of numerical simulation in magnetohydrodynamical approximation.